2021
DOI: 10.3390/molecules26206128
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Quercetin during Cerebral Ischemic Injury Involves Regulation of Essential Elements, Transition Metals, Cu/Zn Ratio, and Antioxidant Activity

Abstract: Cerebral ischemia results in increased oxidative stress in the affected brain. Accumulating evidence suggests that quercetin possesses anti-oxidant and anti-inflammatory properties. The essential elements magnesium (Mg), zinc (Zn), selenium (Se), and transition metal iron (Fe), copper (Cu), and antioxidants superoxide dismutase (SOD) and catalase (CAT) are required for brain functions. This study investigates whether the neuroprotective effects of quercetin on the ipsilateral brain cortex involve altered level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Quercetin (20 mg kg −1 ) significantly increased Mg, Zn, Se, SOD and CAT levels in MCAO rats, while MDA, Fe, Cu and Cu/Zn ratios significantly decreased, suggesting that the neuroprotective effects of quercetin in cerebral ischemic injury include modulation of essential elements, transition metals, and Cu/Zn ratios. 102 Buyang Huanwu decoction, as a drug for the treatment and prevention of ischemic cerebrovascular disease in clinical practice, can significantly inhibit the expression of IL-6 and increase the expression of HIF-1α and vascular endothelial growth factor A (VEGFA). Quercetin, as one of the key compounds of this decoction, showed the potential to protect against cerebral ischemia.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…Quercetin (20 mg kg −1 ) significantly increased Mg, Zn, Se, SOD and CAT levels in MCAO rats, while MDA, Fe, Cu and Cu/Zn ratios significantly decreased, suggesting that the neuroprotective effects of quercetin in cerebral ischemic injury include modulation of essential elements, transition metals, and Cu/Zn ratios. 102 Buyang Huanwu decoction, as a drug for the treatment and prevention of ischemic cerebrovascular disease in clinical practice, can significantly inhibit the expression of IL-6 and increase the expression of HIF-1α and vascular endothelial growth factor A (VEGFA). Quercetin, as one of the key compounds of this decoction, showed the potential to protect against cerebral ischemia.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…A clinical study reveals a relationship between elevated plasma Cu levels and the etiology of Alzheimer’s disease [ 38 ]. A variety of animal studies reveal the fact that cerebral ischemic injury results in an obviously elevated Cu concentration in the affected brain cortex tissues [ 8 , 17 , 18 , 39 ]. Likewise, our present finding proposes that cerebral ischemic insult leads to significant Cu overload in the ischemic brain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Makita et al (2016) and Lin et al (2018) have revealed that the quercetin present is in significant amounts as glycosides associated with a variety of sugar moieties. The bioactive polyphenol structure of quercetin contribute to its anti-inflammatory and neuroprotective properties ( Lesjak et al, 2018 ; Lin et al, 2021 ). Based on an in vivo study, quercetin is highly permeable across the BBB ( Youdim et al, 2014 ).…”
Section: Neuroprotective and Anti-neuroinflammatory Effects Of ...mentioning
confidence: 99%